UJI COBA SISTEM REFRIGERASI ADSORPSI KARBON AKTIF â METANOL - , RUDI RUSTANDI, Ir. Purnomo, MSME.,PhD ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Adsorption Refrigeratian system is an alternatif refrigeration system for facing energy crisis and ozon depletion layer that caused by CFC and HCFC refrigerant of konventional refrigeration systems.The system uses heat energy that came from many sources such as petroleum, natural gas, waste heat from industries or processes, and solar energy. In this research, experimental study of adsorption refrigeration was done with activated carbon â methanol pair. The activated carbon was obtained from local market and the methanol was of laboratory grade. The adsorption refriâgeration system has been made and designed to be able drived by solar energy. The amount of activated carbon used in the system was 2.67 kg and in the experiment electrical heater was used as heat source. It was tested by variated temperature of 140 oC, 150 oC, and 160 oC. 200 grams of water put in the cool box as product to be cooled. The lowest temperatures of evaporator and product as result of cooling process from heating of 140 oC are 14.1oC and 18.0, from heating of 150 oC are 9.7 oC and 16.4 oC, meanwhile from heating of 160 oC are 10.0 oC and 16.2 oC respectively. The reached cooling temperature was still high, far from the water freezing temperature, so this system can not produce ice.